Constitutional Question: Latar Belakang dan Praktik Di Negara Lain Serta Kemungkinan Penerapannya Di Indonesia - I Dewa Gede Palguna (Jurnal Hukum IUS QUIA IUSTUM, 2010)
The adoption of constitutional question mechanism in the constitution court system, (known as constitutional adjudication), regarded as part of providing a maximum protection to the citizen’s constitution rights. The kind of protection is a must-have entity in every law-based nation (in the democratic system). For Indonesia, which has ambition to establish a democracy-based life along with law-based life, as been said in Article 1 Section 2 and 3 in 1945 Constitution, the consideration for adopting a mechanism of “constitutional question” is not impossible to happen. Even more, logically, it is a need.Key word : constitutional question, Constitutional Court of Law, Law-Based nation, Indonesia